(untitled) (Bangladesh Journal of Medical Science, 2025)
Introduction The Nuck duct cyst (NCC) was initially documented by Anton Nuck in 1961 in a female patient. NCC is a rare condition in adult women, and its exact incidence is unknown. A small number of case reports have been documented in the literature. Case report This case report presents a 70-year-old female patient who underwent a conventional mass excision after being diagnosed with a cystic mass in the right inguinal region. The surgical specimen of the patient was histopathologically diagnosed as NCC. Conclusion Although NCC is typically diagnosed peroperatively, it is frequently misdiagnosed preoperatively as an inguinal hernia. Hence, the utilization of radiological imaging techniques is advised to facilitate treatment planning and differential diagnosis. NCC should be considered in the differential diagnosis, particularly in the context of inguinal region pathologies during the reproductive period, given that all of the patients in the aforementioned case reports in the literature are female in their reproductive years. NCC should remain in the differential diagnosis of inguinal region pathologies in elderly female patients in the non-reproductive period, given that the patient in this case report is in the non-reproductive period, in contrast to most patients described in the literature. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 317-320